2012
DOI: 10.1007/s10529-012-0903-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of high quality and yield of RNA from Agaricus bisporus with a simple, inexpensive and reliable method

Abstract: A method for isolating high purity and quantity RNA from Agaricus bisporus which is rich in proteins, carbohydrate, fiber and secondary metabolites, is described. RNA was extracted from mycelium, primordia, sporophores at two development stages and two post-harvest storage stages as well as from pileipellis, inner cap, gill and stipe of the mature sporophore. The A(260)/A(230) and A(260)/A(280) ratios of isolated RNA from fruiting bodies were both ~2 and the yield was about 200 μg/g fresh wt (FW). The yield of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Total RNA was extracted by improved guanidine thiocyanate according to the method of Meng et al. (2012).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted by improved guanidine thiocyanate according to the method of Meng et al. (2012).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA extraction of fresh‐cut button mushrooms was performed referring to Meng, Shen, et al’s (2012) method. According to the reference guide, contaminating genomic DNA was eliminated from the obtained RNA using RNase‐free DNase I (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…The internal control was EF1‐α gene encoding an elongation factor (Meng et al, 2017). The nucleotide sequences of primers used for qPCR were the same as Meng, Shen, et al (2012) have reported. Data were obtained at 72°C.…”
Section: Methodsmentioning
confidence: 99%